Guide to banana bunchy top disease surveillance, control and production recovery - Skilton, Robert A.; Aman, Bonaventure Omondi (2024)
This manual accompanies the course already running online for Banana Bunchy Top Disease Management since 2018. The course presents to you the Banana Bunchy Top disease. This viral disease is a serious threat to the banana cultivation. After an introduction to the banana crop, the course details the transmission mode and the disease spread and presents the symptoms that allow its diagnosis. The course then presents the surveillance methods for BBTD in banana gardens, plantations, and landscapes; and how to control this disease at the local level.